Sentidos e significados da prática de home office: um olhar para o trabalhador do setor financeiro - Luca, Lilian Franco Brito de (2016)
The relationships between humans, society, organizations and labor have been suffering constant changes due to diverse information and communication technology tools. However, not all the implications and consequences of these changes are well-known. Among the changes disseminated by those technologies is the home office. The adoption of this practice has been increased by companies and workers, mainly because of the advantages they perceive from it. There is an estimation that half of the world active population will work at home office by 2050. Previous studies had identified that companies have their space and time boundaries expanded to the worker’s home and personal life and, furthermore, workers highlight the flexibility as a key home office advantage since they can conciliate the company's demands with their personal ones as well as their family activities. However, there is plenty to explore for the home office practice knowledge, its implications for the individual, social relationships and even the contradictions of this work practice. The individual employee is unique, has subjectivity, is part of different social and cultural contexts, and has unique life stories. This worker assigns a meaning and a meaningfulness to things and to the external world phenomena. Thus, these meaning and meaningfulness are not unique, as they are individually built and socially shared. Within this context, the present work aims to identify the meaning and meaningfulness of the home office practice among the workers within the financial sector. Therefore, an exploratory research was done with the financial sector workers, having the cultural socialhistorical approach, initiated by Vygotsky, which has its core principles based on labor activity, meanings, meaningfulness and consciousness, as a background. Moreover, a literature review was performed and it began by understanding not only the social dynamics related to the home office theme but also the characterization of this mode of work as a practice, as well as the logic development of a relationship between the meaning core and the home-office activity. For a better comprehension of the social dynamics of communication and the interaction after the information and communication technology tools, these which have originated and spreaded the home office practice, an explanatory cycle, whose phases are analyzed within the cultural social-historical context, was presented. Finally, among the financial sector workers, it was found six core meanings of the home office practice, which were associated to the balance between their professional and personal life; to the breakthrough of the barrier between these two aspects; to the adaptation of professional and personal routine; to the loneliness of ones and the disorientation of others; and to the prejudgement and contingency due to organized Labor Union strikes. Regarding the home office practice, it was identified that the recommendation received by the company and its managers is not standardized in the financial sector, neither are the technologies provided by companies. Furthermore, it was also verified that, at first, the home office practice is perceived very positively, however, when giving it further thoughts on the theme, some contradictions arose among the workers, such as gaps in the matter of improving the working conditions